Determinação de parâmetros para a avaliação de carcaça em bubalinos machos no Estado do Pará - SEIXAS, Vitória Nazaré Costa (Universidade Federal do Pará, 2014)
This work had as objective to create a protocol for identification of carcass’ quality of male buffalo abated at the Pará State. For this purpose, the work was conducted in two stages. Firstly, were utilized 174 animals for the creation and implementation of the age identification protocol throughout the development of the incisive teeth pairs and the linear measures of hindquarters and height of anterior part, thoracic perimeter and body length. The second stage was the ratification of the preestablished protocol inserted on the evaluation of carcass characteristics through the cold and hot carcass efficiency plus five other typical parameters using 76 abated animals. Was noted the absence of the deciduous corner (fourth pair) in the animals from zero to three months. These corners were definitively noted between three and six months. From six months the incisive deciduous teeth are all presents and established. At the 24th month started the change of the “tweezers” (first tooth pair). Between the 30th and 50th month occurred the change second and third teeth pairs and from the 55th month the change of the fourth teeth pair. From the 55th to the 100th month the animals showed established all incisive permanent teeth. The live weight showed a positive and significant correlation with the linear measures. From the 25,7th to the 30th month was a reduction on the growth tax in consequence of the puberty and development of the fat layer. From 18th there was not significant difference on the carcass characteristics except in relation to the shoulder blade. Thus, we conclude that the beginning of the “tweezers” teeth change is the ideal age for abate where there is the coincidence of the reduction of growth tax and fat layer deposition in the carcass.